Map of teachers’ career paths in brazil - Trein, Laura Dexheimer (2015)
The project “Map of teachers’ career paths in Brazil” is the result of a scientific initiation research comprising data collection and analysis concerning K-12 education public teachers’ career paths of the Brazilian states and their capitals. The data collection was accomplished through the research of the career paths and other materials related to remuneration and teaching career in the Education Department, Legislative Assembly or Municipal Chamber, and Teachers Unions websites of each location. By means of an initial analysis of this material, it was possible to verify the availability of this legislation for the population, the date when each state or capital had their career path enacted, the classifications used to designate the employees concerned by this legislation, and how it is organized. This data collection and initial analysis is the first step of a deeper analysis on teaching career paths in Brazil based on comparative criteria that evaluate the career remuneration and progression in the education networks studied.